Evidence for asymmetric rotation of spins in antiferromagnetic exchange-spring - Y Y Wang; C Song; G Y Wang; F Zeng; F Pan (New Journal of Physics, 2014)
We demonstrate an asymmetric rotation of the antiferromagnetic (AFM) spins in the exchange-spring driven by perpendicularly magnetized Co/Pt. The static and dynamic behaviors of the twisted spin structure are directly revealed by a combination of element specific soft-x-ray absorption spectra and magnetoresistance measurements. X-ray magnetic linear dichroism spectra as a function of AFM thickness clarify the features of the whole exchange-spring, while the interfacial uncompensated spins are identified by the x-ray magnetic circular dichroism spectra. Moreover, the observed tunneling anisotropic magnetoresistance (TAMR) in AFM-based junctions based on this asymmetric rotation provides an electrical approach to monitoring the dynamic twist of the AFM spins. These investigations not only provide a deep insight into the spin structure of the exchange coupling layers but would also advance the development of AFM spintronics.